2020
DOI: 10.3389/fbioe.2020.604793
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of PCR and Isothermal Amplification Techniques Are Suitable for Fast and Sensitive Detection of SARS-CoV-2 Viral RNA

Abstract: The newly identified coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), causes coronavirus disease 2019 (COVID-19) and has affected over 25 million people worldwide as of August 31, 2020. To aid in the development of diagnostic kits for rapid and sensitive detection of the virus, we evaluated a combination of polymerase chain reaction (PCR) and isothermal nucleic acid amplification techniques. Here, we compared conventional PCR and loop-mediated isothermal amplification (LAMP) methods w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
(42 reference statements)
1
14
0
2
Order By: Relevance
“…Recently, a combination of PCR and isothermal nucleic acid amplification known as loop-mediated isothermal amplification (LAMP) techniques was explored. 65 The idea was to introduce the speed of the LAMP techniques and the accuracy of the PCR method in one single platform. It has been shown that combining LAMP and RT-PCR in one assay to develop RT-q(PCR-LAMP) was approximately 100-fold more sensitive than conventional RT-LAMP.…”
Section: Nucleic Acid Amplification Test (Naat)mentioning
confidence: 99%
“…Recently, a combination of PCR and isothermal nucleic acid amplification known as loop-mediated isothermal amplification (LAMP) techniques was explored. 65 The idea was to introduce the speed of the LAMP techniques and the accuracy of the PCR method in one single platform. It has been shown that combining LAMP and RT-PCR in one assay to develop RT-q(PCR-LAMP) was approximately 100-fold more sensitive than conventional RT-LAMP.…”
Section: Nucleic Acid Amplification Test (Naat)mentioning
confidence: 99%
“…In an LAMP experiment, four to six primers are specially designed to identify six to eight regions of the target sequence. 56 , 57 The amplification begins with an inner primer invasion, then a strand-displacing polymerase elongates the primer and separates the DNA duplex. Subsequently, the first product is displaced by another strand, which is extended by an outer primer.…”
Section: Pathogen-based Laboratory Findings For Covid-19 Detectionmentioning
confidence: 99%
“…Specific methods based on quantitative fluorescence polymerase chain reaction (QF-PCR) or isothermal nucleic acid amplification have also been developed (Bustin and Nolan 2020 ; Varlamov et al 2020 ). Nucleic acid amplification tests (NAAT) are highly recommended by the World Health Organization, and they are based on reverse transcription-polymerase chain reaction (RT-PCR).…”
Section: Limits Of Actual Diagnosticsmentioning
confidence: 99%